Implementasi Strategi Pembelajaran Active Knowledge Sharing Terhadap Penguasaan Konsep - Yeni Suryaningsih (Papanda Publisher, 2023)
The background of this research is because the students' academic scores are still below the KKM score. This is because students are passive in learning activities resulting in low student mastery of concepts. The purpose of this research is to apply an active learning strategy to share knowledge to improve students' mastery of concepts. research subjects namely students of class XI MIPA SMAN 1 Sukahaji. The research design used a pretest-posttest control group design. The research instrument was a multiple choice test with a taxonomy cognitive domain developed to measure students' mastery of concepts. The results of the research showed that the application of the active knowledge sharing learning strategy through the non-parametric Mann-Whitney statistical test obtained a Sig (2-tailed) value of 0.000<0.005, meaning there was a significant difference between the experimental class and the control class. This shows that the active knowledge sharing learning strategy can be used as an effort to increase students' mastery of concepts. Keywords: Active Knowledge Sharing, Mastery of Concepts